2010
DOI: 10.3357/asem.2638.2010
|View full text |Cite
|
Sign up to set email alerts
|

Visual Vigilance Performance and Standing Posture at Sea

Abstract: In mild seas, variations in stance width modulate standing posture and influence the performance of computer-based visual tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 17 publications
6
30
4
Order By: Relevance
“…On land, the variability of body position is reduced during performance of demanding visual tasks, such as reading, relative to sway during performance of less demanding visual tasks Stoffregen et al, 2000). Testing experienced maritime crewmembers at sea and Yu et al (2010) confirmed that the positional variability of body sway was reduced during performance of more demanding visual tasks at sea, relative to sway during performance of less demanding visual tasks. Accordingly, we predicted that the variability of body sway would be reduced during performance of more demanding visual tasks on land and at sea.…”
Section: Factors That Influence Standing Body Swaymentioning
confidence: 58%
See 3 more Smart Citations
“…On land, the variability of body position is reduced during performance of demanding visual tasks, such as reading, relative to sway during performance of less demanding visual tasks Stoffregen et al, 2000). Testing experienced maritime crewmembers at sea and Yu et al (2010) confirmed that the positional variability of body sway was reduced during performance of more demanding visual tasks at sea, relative to sway during performance of less demanding visual tasks. Accordingly, we predicted that the variability of body sway would be reduced during performance of more demanding visual tasks on land and at sea.…”
Section: Factors That Influence Standing Body Swaymentioning
confidence: 58%
“…This finding suggests that tuning of body sway to stance width at sea, such as was observed in the present study (cf. Yu et al, 2010;Yu et al, in press) may be related to the risk of seasickness. The tuning would, presumably, be less skillful for novices, which could lead to instability when stance width was mismatched with ship motion or with body orientation relative Downloaded by [University of South Florida] at 16:56 03 November 2014 to the ship (Stoffregen, Chen, Yu, & Villard, 2009).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We have documented relationships between postural activity and visual tasks in mild sea states ( 23,26 ). The present study was conducted on a ship at sea during rough weather conditions.…”
mentioning
confidence: 99%